2005
DOI: 10.1590/s0100-879x2005001100003
|View full text |Cite
|
Sign up to set email alerts
|

Indole ring oxidation by activated leukocytes prevents the production of hypochlorous acid

Abstract: Hypochlorous acid (HOCl) released by activated leukocytes has been implicated in the tissue damage that characterizes chronic inflammatory diseases. In this investigation, 14 indole derivatives, including metabolites such as melatonin, tryptophan and indole-3-acetic acid, were screened for their ability to inhibit the generation of this endogenous oxidant by stimulated leukocytes. The release of HOCl was measured by the production of taurine-chloramine when the leukocytes (2 x 10 6 cells/mL) were incubated at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
1
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 32 publications
(31 reference statements)
3
30
1
1
Order By: Relevance
“…The remaining HOCl was detected by TMB 0.014 mol/L, which has a maximum oxidation at 652 nm. The decrease in TMB absorbance represents the antioxidant activity of each tea (Ximenes et al, 2005).…”
Section: Hocl Scavenging Activitymentioning
confidence: 99%
“…The remaining HOCl was detected by TMB 0.014 mol/L, which has a maximum oxidation at 652 nm. The decrease in TMB absorbance represents the antioxidant activity of each tea (Ximenes et al, 2005).…”
Section: Hocl Scavenging Activitymentioning
confidence: 99%
“…Animals can obtain IAA from intestinal absorption of a diet rich in vegetables or from synthesis from tryptophan in various tissues. 6 Studies have showed that IAA can provide antioxidant activity by inhibiting lipid peroxidation similarly to other indolic compounds 7,8 and provide semen preservation at similar concentrations 9 in water coconut 10 ; in addition, IAA have a topic antiinflammatory action. 11 Recent studies have shown that oral or subcutaneous administration of IAA can promote a possible beneficial effect by increasing the phagocytic capacity of rat neutrophils.…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18] One other study showed that IAA selectively inhibits the excessive production of hypochlorous acid by activated leukocytes, a compound that has been implicated in tissue damage from chronic inflammatory diseases. 19 Recent studies have shown that subcutaneous IAA promotes an increase in phagocytic capacity, is accompanied by alteration in hydrogen peroxide production in neutrophils, but does not show a pro-oxidant effect in leukocytes 20 or liver. 21 The information above led us to study the effect of IAA administered subcutaneously and by gavage to rats at low doses (equal to or less than 40 mg of IAA per kg of body mass) on neutrophil functions and cell death of neutrophils and lymphocytes.…”
Section: Introductionmentioning
confidence: 99%